2013
DOI: 10.5194/nhessd-1-3485-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptability and transferability of flood loss functions in residential areas

Abstract: Abstract. Flood loss modeling is an important component within flood risk assessments. Traditionally, stage-damage functions are used for the estimation of direct monetary damage to buildings. Although it is known that such functions are governed by large uncertainties, they are commonly applied – even in different geographical regions – without further validation, mainly due to the lack of data. Until now, little research has been done to investigate the applicability and transferability of such damage models… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…For instance, [16] revealed, that additional explanatory variables besides the water depth improve the predictive capability in a spatial and temporal transfer context, i.e., when the models are transferred to different regions and different flood events. [9] clearly demonstrated that loss models are better transferable if the underlying empirical data are taken from region similar or near to the study area. Yet it is concluded that a temporal and spatial transferability of models is necessarily linked to an adjustment of the input data regarding the vulnerability of elements at risk and study site characteristics.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…For instance, [16] revealed, that additional explanatory variables besides the water depth improve the predictive capability in a spatial and temporal transfer context, i.e., when the models are transferred to different regions and different flood events. [9] clearly demonstrated that loss models are better transferable if the underlying empirical data are taken from region similar or near to the study area. Yet it is concluded that a temporal and spatial transferability of models is necessarily linked to an adjustment of the input data regarding the vulnerability of elements at risk and study site characteristics.…”
Section: Introductionmentioning
confidence: 97%
“…As a measure for acceptable loss estimations and rating tool for the overall model accuracy, a bootstrap procedure with 10,000 random samples with replacement was applied to all reported building loss data. In accordance with [38] and [9], the 2.5th and 97.5th percentile of the total, mean and median building loss were hence calculated to obtain a 95 % confidence interval of the reported building loss records. Eventually, all modelled building losses that fell within this bootstrap interval were assumed to be acceptable.…”
Section: Derivation and Adaptation Of The Flood Loss Modelmentioning
confidence: 99%
See 3 more Smart Citations